Search for lepton-flavor-violating tau decays to ℓα at Belle - The BELLE collaboration; K. Uno; K. Hayasaka; K. Inami; H. Aihara; R. Ayad; Sw. Banerjee; K. Belous; J. Bennett; M. Bessner; D. Biswas; D. Bodrov; et al. (Journal of High Energy Physics)
Abstract We report a search for the lepton-flavor-violating decays τ ± → ℓ ± α (ℓ = e, μ), where α is an undetected spin-0 particle, such as an axion-like particle using 736 × 106 tau lepton pairs collected by the Belle detector at the KEKB asymmetric-energy e + e − collider. We find no evidence of signal and obtain the most stringent upper limits on the branching fractions at 95% confidence level: $$\mathcal{B}$$ (τ ± → e ± α) < (0.4–6.4) × 10 −4 and $$\mathcal{B}$$ (τ ± → μ ± α) < (0.2–3.5) × 10 −4 at 95% confidence level for an α mass in the range 0.0 ≤ m α ≤ 1.6 GeV/c 2.